Plant-based Natural Products for Wound Healing: A Critical Review - Ramalingam, Shalini; Chandrasekar, Moola J. N.; Nanjan, Moola J. (Current Drug Research Reviews, 2022)
Wound healing is an intricate process consisting of four overlapping phases, namely hemostasis, inflammation, proliferation, and remodelling. Effective treatment of wounds depends upon the interaction of appropriate cell types, cell surface receptors, and the extracellular matrix with the therapeutic agents. Several approaches currently used for treating wounds, such as advanced wound dressing, growth factor therapy, stem cell therapy, and gene therapy, are not very effective and lead to impaired healing. Further, repeated use of antibiotics to treat open wounds leads to multi- drug resistance. Today there is considerable interest in plant-based drugs as they are believed to be safe, inexpensive, and more suitable for chronic wounds. For example, a large number of plant- based extracts and their bioactive compounds have been investigated for wound healing. In recent years the structural and mechanistic diversity of natural products have become central players in the search for newer therapeutic agents. In the present review, a thorough critical survey of the traditionally used plant-based drugs used worldwide for wound healing with special reference to the natural products/bioactive compounds isolated and screened is presented. It is hoped that this review will attract the attention of the research community involved in newer drug design and development for wound healing.
Keywords: Wound healing